Detrimental external factors that influence performance of students who repeat psychological satistics - Haque, Hamed S; Abd Hamid, Harris Shah (2014)
Psychology students generally dread their undergraduate statistics course. The current study explored the detrimental external factors that influence students to perform poorly in statistics courses. In-depth interviews were conducted on six undergraduate psychology students from International Islamic University Malaysia who failed a statistics course and the data was analyzed using thematic analysis. Eight factors were obtained (with a total of 19 sub-factors) and were arranged under the Lecturer, Social Support, Administrative, and Environmental categories. The findings of the study would provide statistics lecturers with a better understanding of why many of their students face difficulty in the course.